Study of resistance to leaf and stem rusts in Triticum aestivum–Aegilops speltoides lines - S. N. Sibikeev; S. A. Voronina; E. D. Badaeva; A. E. Druzhin (Вавиловский журнал генетики и селекции)
Presently, the use of bread wheat introgression lines resistant to pathogens in practical breeding is hampered by the lack of their cytogenetic characteristics, data on the genetic control of disease resistance, and influence of alien genetic material on grain productivity and quality. For the solution of these problems, two wheat–Aegilops speltoides lines, L195 and L200, developed at ARISER and resistant to leaf and stem rusts were studied. These lines were produced by crossing of spring bread wheat cultivars to line L26b-4. Cytogenetic analysis of the lines involved C-banding, meiotic analyses, and FISH with pAs1 and Fat. It allowed the rust resistance genes, efficient against both rust types, to be mapped to a 2D-2S translocation in both lines. Genetic analysis revealed tight linkage of leaf rust resistance genes from Ae. speltoides to gametocidal genes and absence of susceptible plants from the F2 hybrids and subsequent generations. Exceptions were found only in hybrid combinations with lines L2032 and L583: occasional susceptible plants were noted  in the F2 and subsequent generations. Evaluation of lines L195 and L200 revealed high resistance to Ug99 + Lr24 (TTKST) and a local Saratov population of stem rust. The prebreeding studies of lines L195 and L200 showed their benefits in breeding for grain productivity in comparison with the recipient cultivar L503 and good bread-making quality. Due to the complex of agronomical traits and high resistance to leaf and stem rusts, lines L195 and L200 can be considered promising donors for commercial bread wheat breeding.